HANDICRAFT COOPERATION OF THE NORTH CAUCASUS IN THE CONTEXT OF A NEW ECONOMIC POLICY (1921–1929) - A. A. Panarin (Гуманитарные и юридические исследования)
The article discusses the activities of the handicraft commercial cooperation in the North caucasus in the conditions of a new economic policy. The process of the formation of hand-fishing cooperation in the early 1920s is analyzed. It is characteristic of its main organizational principles and the ideas of the leadership of the Bolshevik party about the place of production cooperation in the structure of the Soviet economy. The economic activity of hand-commercial cooperation in various parts of the North caucasus is covered, its role is noted in supplying industrial enterprises, the Red Army and the population with various types of products. The measures taken by partygovernment agencies and cooperative unions involvement in the cooperation of single shutters. Low results are noted in solving this problem due to the organizational weakness and limited material means of cooperative unions, as well as the desire of single handy to preserve their independence. The class approach was emphasized who was guided by the Soviet state in the development of hand-commercial cooperation in the late 1920s. The influence of the 1920-1930s administrative-command system on the process of transformation of the hand-commercial cooperation and its final transformation into the slave element of the planning economy is shown. An assessment is given to the main results of the development of handicraft cooperation in the North caucasus in the conditions of NEP.